2013
DOI: 10.1111/nph.12595
|View full text |Cite
|
Sign up to set email alerts
|

Laterally resolved speciation of arsenic in roots of wheat and rice using fluorescence‐XANES imaging

Abstract: SummaryAccumulation of arsenic (As) within plant tissues represents a human health risk, but there remains much to learn regarding the speciation of As within plants.We developed synchrotron-based fluorescence-X-ray absorption near-edge spectroscopy (fluorescence-XANES) imaging in hydrated and fresh plant tissues to provide laterally resolved data on the in situ speciation of As in roots of wheat (Triticum aestivum) and rice (Oryza sativa) exposed to 2 lM As(V) or As(III).When exposed to As(V), the As was rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 39 publications
(82 reference statements)
1
44
1
Order By: Relevance
“…First, laterally resolved data on the speciation of Mn within plant tissues was obtained using the Maia detector system at the Australian Synchrotron. With fluorescence-XANES imaging, speciation data (i.e., XANES spectra) were collected for every pixel in the map as explained by Kopittke et al (2014). This procedure differs from the typical approach of obtaining micro-XANES spectra at specific individual locations.…”
Section: Manganese Speciation In Plant Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…First, laterally resolved data on the speciation of Mn within plant tissues was obtained using the Maia detector system at the Australian Synchrotron. With fluorescence-XANES imaging, speciation data (i.e., XANES spectra) were collected for every pixel in the map as explained by Kopittke et al (2014). This procedure differs from the typical approach of obtaining micro-XANES spectra at specific individual locations.…”
Section: Manganese Speciation In Plant Tissuesmentioning
confidence: 99%
“…7; Supplemental Fig. S15A) using the energy association module in GeoPIXE (Kopittke et al, 2014). Three Mn populations (other than the background pixels) were identified in which Mn concentration changed from the base to the tip ( Fig.…”
Section: Manganese Speciation In Plant Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced imaging techniques used by different researchers have revealed elevated levels of As [18][19][20][21] or Se (as selenite) [22] associated with rice root apices where the Casparian bands are purportedly absent [12,13]. However, because some of these images [18,19] were generated from whole root mounts and not cross-sections, it was unclear if the elevated As signal in those studies was predominantly on the inside of the roots or on the outside of roots associated with Fe plaques (or both).…”
Section: Introductionmentioning
confidence: 99%
“…However, because some of these images [18,19] were generated from whole root mounts and not cross-sections, it was unclear if the elevated As signal in those studies was predominantly on the inside of the roots or on the outside of roots associated with Fe plaques (or both). Other researchers have successfully used computed tomography or modeling approaches to estimate the influx of As in root apices in rice, wheat, and cowpea roots in short-term studies [20,23]. Ma et al [24] demonstrated that lateral roots are important for Si transport in rice, but the importance of these zones for As(III) i root-uptake has only recently been investigated [25].…”
Section: Introductionmentioning
confidence: 99%